Obstetric outcomes after uterine balloon tamponade for postpartum hemorrhage - Adhikari, HN; Pandey, A; Singh, M; Sinha, K (Devdaha Medical Journal, 2025)
Introduction: Postpartum hemorrhage (PPH) remains a leading cause of maternal mortality globally, particularly in low-resource settings. Balloon tamponade, a minimally invasive, uterus-preserving intervention, is increasingly being used to manage refractory PPH.Methods: A hospital-based observational study was conducted at Nepalgunj Medical College from November 2024 to May 2025. A total of 39 women with refractory primary PPH requiring balloon tamponade were included. Maternal demographic characteristics, obstetric variables, balloon tamponade parameters, and clinical outcomes were analyzed using SPSS version 26.0. Categorical variables were compared using the chi-square or Fisher’s exact test, and continuous variables using the independent samples t-test. A p-value